Advances in human chorionic gonadotropin detection technologies: a review. (October 2017) - Fan, Jing; Wang, Mandy; Wang, Chengyin; Cao, Yu
Human chorionic gonadotropin (HCG) is a glycoprotein secreted by placental trophoblast cells in pregnancy. HCG is a heterodimer composed of two different α- and β-subunits, with the latter being unique to HCG. As well as being the most important diagnostic markers for pregnancy, HCG is also a tumor marker, therefore, quantitative detection of HCG is of great value. Numerous advanced technologies have been developed for HCG concentration detection including electrochemical immunoassay, chemiluminescent immunoassay, fluorescence immunoassay, resonance scattering spectrometry, atomic emission spectrometry, radioimmunoassay, MS and so on. Some have pursued simple and easy operation, while others have emphasized on accuracy and applications in clinical medicine. This review provides a comprehensive summary of various methods of detecting HCG.